Isolated femoral artery revascularisation with or without iliac inflow improvement: a less invasive surgical option in critical limb ischemia - Peters, Andreas; Meisenbacher, Katrin; Kronsteiner, Dorothea; Bisdas, Theodosios; Torsello, Giovanni; Böckler, Dittmar; Bischoff, Moritz (Vasa, 2021)
Summary:Background: Isolated femoral artery revascularisation (iFAR) represents a well-established surgical method in the treatment of peripheral arterial disease (PAD) involving common femoral artery disease. Data for iFAR in multilevel PAD are inconsistent, particularly in patients with critical limb ischemia (CLI). The aim of the study was to evaluate the outcome of iFAR in CLI regarding major amputation and reintervention and to identify associated risk factors for this outcome. Patients and methods: The data used have been derived from the German Registry of Firstline Treatment in Critical Limb Ischemia (CRITISCH). A total of 1200 patients were enrolled in 27 vascular centres. This sub-analysis included patients, which were treated with iFAR with/without concomitant iliac intervention. For detection of risk factors for the combined endpoint of major amputation and/or reintervention, selection of variables for multiple regression was conducted using stepwise forward/backward selection by Akaike’s information criterion. Results: 95 patients were included (mean age: 72 years ± 10.82; 64.2% male). Of those, 32 (33.7%) participants reached the combined endpoint. Risk factor analysis revealed continued tobacco use (odds ratio [OR] 2.316, confidence interval [CI] 0.832-6.674), TASC D-lesion (OR: 2.293, CI: 0.869-6.261) and previous vascular intervention in the trial leg (OR: 2.720, CI: 1.037-7.381) to be associated with reaching the combined endpoint. Conclusions: iFAR provides a reasonable, surgical option to treat CLI. Lesion length (TASC D) seems to have a negative impact on outcome. Further research is required to better define the future role of iFAR for combined femoro-popliteal lesions in CLI - best in terms of a randomised controlled trial.
Gesehen am 03.11.2021